Results of a Sociological Survey on the Needs of Drug Safety Monitoring Specialists for Information on the Creation of the Pharmacovigilance System Master File - N. G. Goloenko; R. I. Yagudina; A. Yu. Kulikov; V. G. Serpik; M. V. Protsenko; D. G. Karapetyan (Безопасность и риск фармакотерапии, 2020)
The Rules of Good Pharmacovigilance Practice of the Eurasian Economic Union oblige developers and marketing authorisation holders to implement a pharmacovigilance system that has to be described in the pharmacovigilance system master file (PSMF). Analysis of public sources revealed lack of data describing the creation of a PSMF. Therefore, the creation of a PSMF and keeping it up to date may prove challenging for pharmacovigilance specialists.The aim of the study was to identify information needs of pharmacovigilance specialists by carrying out a sociological survey.Materials and methods: the authors used information analysis methods (review and analysis of regulatory documents and scientific literature) and sociological methods (a questionnaire for pharmacovigilance specialists).Results: the analysis helped to identify the following master file sections that present problems for specialists: sources of safety data; annexes to the master file; quality system; changes in the pharmacovigilance system that may result in an additional request from the competent authorities, etc.Conclusions: the authors identified the most relevant topics for additional training: “Pharmacovigilance system documents” and “Pharmacovigilance system master file”. The results of the study are helpful for elaboration and updating of additional training programmes for pharmacovigilance specialists.